The effects of maternal environmental tobacco smoke exposure on periodontal health and mother-infant bonding in relation to salivary cotinine level - Salim , Nada Z; Diab , Ban S (Journal of Baghdad College of Dentistry, 2023)
Background: Environmental tobacco smoking is produced by active smokers burning the tip of a cigarette and breathed by nonsmokers and measured by cotinine level. It has the potential to raise the risk of periodontal disease. One of the most frequent chronic diseases in adults is periodontal disease. The lower maternal-fetal attachment has been found to predict smoking status in previous studies, but no research has examined whether maternal-fetal attachment predicts environmental tobacco smoking. This study assessed the effects of maternal environmental tobacco smoke exposure on periodontal health and mother-infant bonding concerning salivary cotinine levels. Materials and methods: This is a comparative cross-sectional study comparing environmental tobacco smoke on exposed and non-exposed mothers aged between 20-35 years with their infants aged up to one year who attended primary health care centers in rural areas of AL-Karkh sector/Baghdad. Along with the essential socio-demographic data, a secondhand smoke exposure scale and postpartum bonding questionnaire were employed. Collection of unstimulated saliva from mothers was done according to Navazesh and Kumer in 2008. After that, the clinical Assessment of gingival bleeding and periodontal pockets was performed by using Community Periodontal Index according to the world health organization in 1997. Results: Out of 150 subjects,67(44.66%) were exposed to environmental tobacco whereas the non-exposed mothers were composed of 83 (55.33%). The highest mean number of CPI0(healthy gingiva) and CPI1(gingival bleeding) were among the non-exposed mothers while the highest mean number of CPI2(dental calculus), CPI3 (shallow pocket 4-5mm) and CPI4(deep pocket 6mm or more) were among the exposed mothers. The mean value of cotinine level among the non-exposed mothers was lower than exposed mothers with significant results. A higher salivary cotinine level was linked to a lower maternal-fetal bonding score. Conclusions: Mother’s exposure to environmental tobacco smoke significantly negatively impacts periodontal disease. Furthermore, mothers who have a stronger sense of attachment and affiliation to their fetus have lower salivary cotinine concentrations than mothers who have a less sense of fetal attachment.